Manejo geral de suínos confinados em sistema intensivo de produção – IFTO - Araguatins/TO 2015 - Gomes, Samilla Costa (Universidade Federal do Tocantins, 2023)
Training curricular supervised was held at the Federal Institute of Education, Science and Tocantins Technology (IFTO) Campus Araguatins in the corresponding period of may 11 to july 11, 2015, in order to relate the theoretical knowledge acquired in the classroom with practices of daily activities experienced in the pig industry such as general management in various stages of production, as well as nutritional ; health ; waste and zootechnical bookkeeping of the flock during any stage of the period. During the internship was possible to follow the general management in the different phases : reproduction, pregnancy, maternity, nursery, growing and finishing when performing nutritional management practice, health, waste and zootechnical bookkeeping of the herd. The activities developed during the supervised traineeship allowed through management practices complement the Knowledge acquired during the course of Animal Science , leading to improvement in pig farming area.